Reform des familiengerichtlichen Verfahrens - 1. Familienrechtliches Forum Göttingen - Lipp, Volker; Schumann, Eva; Veit, Barbara (Universitätsverlag Göttingen, 2009)
This volume documents the proceedings of the first "Family Law Forum which took place in Göttingen on June 28 2008. Just before the conclusion of the legislative process, reknowned experts from science, policy and practice discussed the new "Law on the Proceedings in Family Matters and in Matters of Voluntary Systems of Law," (FamFG) that came into effect in September 2009. This volume includes an extensive overview of the features of the new family law and analysis and opinions on various aspects of the law.